2001
DOI: 10.1029/1999rs002310
|View full text |Cite
|
Sign up to set email alerts
|

Fading timescales associated with GPS signals and potential consequences

Abstract: Abstract. The effect of equatorial ionospheric scintillations on the operation of GPS receivers is investigated, with special attention given to the effect of scintillation timescales on the code division multiple access (CDMA) protocol used by GPS. We begin by examining the timescales of scintillation fades modeled as a horizontally drifting pattern whose timescales are determined by the Fresnel length and the drift speed. The model is tested by comparing the speed, determined by dividing the Fresnel length b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
124
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 18 publications
3
124
0
Order By: Relevance
“…For the design of receiving systems, important considerations should be the fade margin and adaptive capability of the receiver to maintain the lock condition during the period of scintillation. A study of variability in scintillation interval along with fade depth is important for deciding the adaptive capability of the receiving system as loss of tracking and acquisition time are mostly dependent on these factors (Kinter et al, 2001). A distribution of an average scintillation patch duration at three locations is depicted in Fig.…”
Section: General Features Of Scintillation Variabilitymentioning
confidence: 99%
“…For the design of receiving systems, important considerations should be the fade margin and adaptive capability of the receiver to maintain the lock condition during the period of scintillation. A study of variability in scintillation interval along with fade depth is important for deciding the adaptive capability of the receiving system as loss of tracking and acquisition time are mostly dependent on these factors (Kinter et al, 2001). A distribution of an average scintillation patch duration at three locations is depicted in Fig.…”
Section: General Features Of Scintillation Variabilitymentioning
confidence: 99%
“…The movement of the ionospheric irregularities relative to the signal path converts these spatial fluctuations, due to diffraction effects, into temporal fluctuations, which, due to the diffraction effects, are observed as scintillations in the GPS received signal (Wanninger, 1993). It was observed that during strong scintillation, deep amplitude fades or large phase fluctuations may cause signal disruptions in the receiver-satellite link (Skone et al, 2000;Kintner et al, 2001). Amplitude scintillations can be monitored by the time series of C/N 0 (signalto-noise ratio) provided by the GPS output, and phase scintillations result from sudden changes in ionospheric refraction or from diffraction effects.…”
Section: Introductionmentioning
confidence: 99%
“…Scintillation is characterized by rapid fluctuations in the amplitude and phase of transionospheric radio signals as they pass through small-scale plasma density irregularities in the ionosphere [Kintner et al, 2001, and references therein]. The occurrence of scintillation shows large day-to-day variability with local time, season, latitude, longitude, as well as solar and geomagnetic activity.…”
Section: Introductionmentioning
confidence: 99%